2010
DOI: 10.1002/aoc.1690
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, electrochemistry and evaluation of biological activities of some ferrocenyl Schiff bases

Abstract: Synthesis of ferrocenyl Schiff bases (1-6) was carried out by the condensation reaction of 4-ferrocenyl aniline with different substituted aromatic aldehydes and acetyl acetone. Compounds were characterized by physical measurements, elemental analysis, FT-IR, 1 H-NMR and 13 C-NMR spectroscopy. Single crystal X-ray analysis of compound 2 showed the co-planarity of both aromatic rings connected by a C-N double bond. Compounds demonstrated reversible one-electron redox behavior and their peak currents were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…There was no general trend of cytotoxicity observed by varying the spacers except the fluorine based hexafluoro isopropylidene group which showed more cytotoxic behavior. However all the test compounds showed concentration dependent toxic behavior [17].…”
Section: Biological Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…There was no general trend of cytotoxicity observed by varying the spacers except the fluorine based hexafluoro isopropylidene group which showed more cytotoxic behavior. However all the test compounds showed concentration dependent toxic behavior [17].…”
Section: Biological Activitymentioning
confidence: 95%
“…Brine shrimp (Artemia salina) lethality assay was performed to test the toxicity of poly(azomethine)esters and their monomer [17]. The eggs of brine shrimps were hatched in artificial sea water solution for 48 h. The sample was prepared by dissolving 1 mg of each compound in 1 ml of solvent.…”
Section: Brine Shrimp Cytotoxic Assaymentioning
confidence: 99%
“…On the example of Schiff bases with ferrocenyl group antioxidant effect has shown in the reaction of DNA with initiator (AAPH) . It was shown that ferrocifens and Schiff bases with ferrocenyl moiety do not exhibit damaging effect on DNA . Here we evaluate the influence of compounds 1–4 on AAPH induced oxidative damage of the DNA and Fe 3+ ‐induced lipid peroxidation of rat (Wistar) brain homogenate as a non‐enzymatic process.…”
Section: Resultsmentioning
confidence: 99%
“…Ferrocenyl Schiff bases demonstrate different biological activity: anticancer, antifungal, radical scavenging, antioxidant activity and the DNA protection . The ability of ferrocenyl‐containing compounds to scavenge radicals is caused by the presence of redox‐active fragment with pronounced antioxidant properties such as phenol, catechol or curcumin .…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor activities of a series of ferrocenyl compounds showing lower toxicity in comparison to clinically used drugs has also been reported in literature [11]; [36], [37]. Zaheer et al reported on the low cytotoxicity, antifungal and DNA protection activities of some synthesized ferrocenyl Schiff bases [38]. The novel ferrocene derivatives synthesized by Yavuz and Yilldirim, displayed excellent antimicrobial activity [39].…”
mentioning
confidence: 77%